A choreography of nicotinic receptors directs the dopamine neuron routine. - Ungless, M; Cragg, S (2006)
Modulation of the mesocorticolimbic dopamine system by nicotinic acetylcholine receptors (nAChRs) is thought to play an important role in both health and addiction. However, a clear understanding of how these receptors regulate in vivo firing activity has been elusive. In this issue of Neuron, Mameli-Engvall and colleagues report an impressive and thought-provoking series of in vivo experiments combining single-unit recordings from dopamine neurons with nAChR subunit deletions and region-specific lentiviral subunit re-expression.